THE EFFECTIVENESS OF CHUNKING STRATEGY IN IMPROVING READING COMPREHENSION AT EFL STUDENTS - Faza Elsa Sefrina; Ida Ayu Panuntun (Universitas PGRI Palembang, 2025)
This study explores the efficacy of the chunking strategy in enhancing reading comprehension among students learning English as a Foreign Language (EFL). A total of 62 students from two classes X TKJ 1 and X TKJ 2 at SMK Muhammadiyah Karanganyar participated in the research. Employing a quantitative approach through a quasi-experimental design, the study utilized pre-tests, post-tests, and questionnaires as instruments for data collection. The pre-test and post-test results were analyzed using SPSS 25, with the Mann-Whitney U Test yielding a significance value of 0.002. This statistical outcome suggests that the application of the chunking strategy had a significant and positive effect on students' reading comprehension performance. Accordingly, the findings affirm that the chunking strategy serves as an effective instructional method for fostering reading comprehension among EFL learners.